Evaluating the Quality of Corporations' Commitment to their Economic Responsibilities: A Theoretical Study to enrich the Thought of CSR - Younis A. Battal Saleh (Jurnal Inovasi Bisnis dan Kewirausahaan, 2022)
Abstract -- The researcher presented the following argument, which is that, making a profit is not a sufficient indicator of the corporation’s commitment to its economic responsibility. The profit figure appearing in the financial statements indicates that there is a commitment by the corporation to its economic responsibility, but it does not reflect the level of quality of that commitment -whether the commitment is poor, good or excellent. For this reason, the researcher suggested the necessity of evaluating the economic responsibilities of the departments that make up the organizational structure of the corporation and contribute to achieving that profit. Unfortunately, the thought of CSR did not specify and describe those responsibilities. Therefore, this study is conducted as an attempt to get out of this predicament. This study aims to identify and describe the economic responsibilities of the departments included in the FOS of the corporation as the economic entities that contribute to achieving profit and through which the quality of the corporation's commitment to its economic responsibility can be judged. To determine and describe the economic responsibilities of the departments that make up the organizational structure in any corporation, the concepts of effectiveness and efficiency in accomplishing the functions assigned to those departments were selected as an approach to define those responsibilities, with the need to define criteria for evaluating the quality of effectiveness and efficiency.Through the concepts of effectiveness and efficiency in completing functions, this study was able to determine and describe the economic responsibilities for the senior management, the purchasing department, the production department and the marketing department that were chosen to be the subject of this study as they made the most impact on the profit figure. The idea of this study, which depends on the concepts of effectiveness and efficiency in performing the functions, can be adopted in defining and describing the economic responsibilities of the departments included in the FOS of any for-profit corporation. This study is an enrichment of the thought of CSR, and it will be considered as the starting point for many studies and research in this field.